SENSITIVITY AND SPECIFICITY OF RAPID TEST BRUGIA MALAYI - Kumalasari, Tri Novia (Biomedical Journal of Indonesia, 2019)
Filariasis is a chronic infectious disease caused by the filarial worm that attacks the lymph veselle and lymph nodes. There are three species of filarial worms known to cause 90% of filariasis cases they were: Wuchereria bancrofti, Brugia malayi and Brugia timori. Microscopic examination of the thick blood clots using peripheral blood of patients at night is a conventional technique. In the global filariasis elimination program, WHO has recommended serodiagnosis methods. For filariasis Brugia, the best serodiagnosis method currently available is the detection of IgG4 anti-filarial antibodies. Research Objectives were to determine the sensitivity and specificity of the Brugia Rapid Test comparing to blood clots method with Giemsa staining in detecting Brugia malayi in the village of Sungai Rengit Murni Talang Kelapa District Banyuasin Regency. The Method used in the study was diagnostic test. The research was conducted in the village of Sungai Rengit Murni Banyuasin Regency on June 20, 2013. The number of samples were 80 people taken using simple random Sampling. Giemsa staining and Brugia Rapid Test were used as examination method. Based on the findings of the 80 samples examined, the examination result using Giemsa method was 0 (0%) and the method of Brugia Rapid were 22 people (27.5%) The Sensitivity of Brugia Rapid Test compared to Giemsa method was 0%, the spesifisitasnya was 72,5%; 0% positive predictive value and 100% negative predictive value.